THE PLACE OF INTERNATIONAL COOPERATION FOR THE REPUBLIC OF UZBEKISTAN IN THE FIELD OF COMBATING ILLEGAL FOREIGN LABOR MIGRATION AND HUMAN TRAFFICKING: A COMPLEX SCIENTIFIC-ANALYTICAL (World Bulletin of Management and Law, 2026)
This scientific article analyzes the current state and prospects of international cooperation of the Republic of Uzbekistan in combating illegal external labor migration and human trafficking. The study examines the geographical diversification of migration flows, particularly the shift from the Russian Federation to other destinations (Germany, South Korea), and its economic implications. It highlights the strategic partnership with Germany on migration and mobility , challenges within the EPS system with South Korea , and cooperation mechanisms with international organizations (IOM, UNODC). Special attention is paid to the efficiency of the rehabilitation system for victims of human trafficking and legislative reforms in this sphere.